Penerapan Algoritma Rivest-Shamir-Adleman (RSA) pada Enkripsi Uniform Resource Locator (URL) Website untuk Keamanan Data - Trisnawati, Theodora Tantri; Yurinanda, Sherli; Syafmen, Wardi; Multahadah, Cut (Universitas Negeri Gorontalo, 2023)
PT. Rezeki Surya Gasindo is a company that uses websites to store important company data, one of which is customer personal data. PT. Rezeki Surya Gasindo's website is protected by a login system. However, a login system alone is not enough to protect the data stored on the website from cases of data theft by third parties. One solution to this problem is to encrypt the website's Uniform Resource Locator (URL) to increase the security level of data stored on the website. In this research, the Rivest-Shamir-Adleman (RSA) algorithm is used for the encryption process. The aim of this research is to determine the process of applying the Rivest-Shamir-Adleman (RSA) algorithm to the Uniform Resource Locator (URL) encryption of the PT. Surya Gasindo's website. The success of applying encryption with the RSA algorithm is observed from changes in the get parameter value that appears in the URL bar. The encrypted message is the customer, the get parameter in the Customer menu, which contains the consumer's personal data. By choosing two large prime numbers, namely 151 and 173, and taking one of the public keys/encryption keys, namely 16379, the result is that the get parameter in the URL bar has changed to the code string 5a9cb05811aa6e4c. The RSA algorithm has been successfully applied to the website URL.